Analisis Pengaruh Speed Terhadap Fuel Ratio Alat Angkut Sany SKT90S-35 Pada Kegiatan Pengupasan Overburden Pit South di PT. Anugerah Covindo Indonesia - Heri Permana; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2023)
PT. Anugerah Covindo Indonesia is a coal mining service company as a contractor in the open pit area, one of its jobsites is GPU (Gorbi Putra Utama) Pit South Beringin II Village, Rawas Hilir District, North Musi Rawas Regency, South Sumatra Province. Based on the problems in the field, it is known that there are not ideal road geometries such as straight road widths and bends which are still lacking in grade which exceeds 12%. With the condition of the road geometry that is not ideal, it will affect the total resistance of the vehicle so that it will affect the speed of the conveyance that crosses it which in turn will cause the productivity of the transportation equipment and the value of the fuel ratio of the transportation equipment to increase. This study aims to analyze how the ideal road geometry is on the road, analyze the actual total resistance value and after repairs and analyze the speed value and fuel ratio value of the conveyance both in actual conditions and after repairs have been made. The type of research used is applied research which aims to find solutions to certain problems with data in the form of qualitative and quantitative data. From the results of the calculations, the minimum width on straight roads is 12.5 m, on bends is 17.545 m, and the road grade must be reduced with a maximum grade value of 12%. The total resistance value has decreased so that the productivity of the transportation equipment has increased and the fuel ratio value of the SANY SKT 90S transportation equipment has decreased. The actual productivity of the transportation equipment was 117,260, BCM/month increased to 160,256.7 BCM/month, while the fuel ratio for the actual condition of the transportation equipment was 0.48 ltr/bcm, which decreased to 0.35 ltr/bcm.